A Novel NIR Fluorescent Nanoprobe Targeting HER2-Positive Breast Cancer: Tra-TTR-A. (30th December 2021) - Chen, Meijuan; Lin, Zhousheng; Yao, Guangyu; Hong, Xi; Xue, Xiaolei; Chen, Lujia
Abstract : TTRE, a photosensitizer molecule, has excellent biofluorescence imaging performance and effective antitumor properties for breast cancer. However, its application in breast cancer treatment is limited due to poor tumor selectivity and lack of targeting ability. In this study, TTRE and trastuzumab were combined to synthesize Tra-TTR-A, a novel near-infrared fluorescent nanoprobe for HER2 positive breast cancer. The targeting and antitumor abilities of Tra-TTR-A in breast cancer were also investigated. Like TTRE, Tra-TTR-A has a stable structure with remarkable optical properties and in vivo imaging capacity. However, Tra-TTR-A not only inhibits tumor growth by generating reactive oxygen species but also kills tumor cells by trastuzumab. In this study, Tra-TTR-A, a new type of near-infrared fluorescent nanoprobe that targets HER2-positive breast cancer, was successfully synthesized. Tra-TTR-A could be used in in vivo imaging, targeted photodynamic therapy, and diagnosis and treatment for breast cancer.